2012
DOI: 10.1103/physreva.85.043821
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase transition in the Dicke model with critical and noncritical entanglement

Abstract: We study the quantum phase transition of the Dicke model in the classical oscillator limit, where it occurs already for finite spin length. In contrast to the classical spin limit, for which spin-oscillator entanglement diverges at the transition, entanglement in the classical oscillator limit remains small. We derive the quantum phase transition with identical critical behavior in the two classical limits and explain the differences with respect to quantum fluctuations around the mean-field ground state throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 24 publications
(46 reference statements)
1
110
2
Order By: Relevance
“…We may flip the coin and consider the 'classical limit' of the harmonic oscillator instead which would be represented by ω/Ω → 0 [48]. In a set of independent papers it was realized that in such a limit critical-like behaviour and a symmetry breaking are also possible in the Rabi model [10,11,12]. for the 50 lowest energies, and C = 2500 and non-scaled frequencies ω = Ω = 1.…”
Section: The Quantum Rabi Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…We may flip the coin and consider the 'classical limit' of the harmonic oscillator instead which would be represented by ω/Ω → 0 [48]. In a set of independent papers it was realized that in such a limit critical-like behaviour and a symmetry breaking are also possible in the Rabi model [10,11,12]. for the 50 lowest energies, and C = 2500 and non-scaled frequencies ω = Ω = 1.…”
Section: The Quantum Rabi Modelmentioning
confidence: 99%
“…Following Refs. [10,11,12,13] we also analyzed the so called classical limit of the quantum Rabi and the JC models. In this limit the two models become critical, and there are many similarities with the critical behaviour of the Dicke and TC models.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…All these factors might contribute to the fact that the physics of the quantum Rabi model still has not been fully explored. Thus, one should face the challenge of using an intuitive way to understand the Rabi model in a general case, in which extensive physics phenomena might be involved [49][50][51][52][53][54]. In our previous work [55], we found that the deformed polaron picture is a good starting point to study the Rabi model in the whole parameter regime, and furthermore, a ground state phase diagram of the Rabi model has been extracted and some underlying physics unveiled.…”
Section: Introductionmentioning
confidence: 99%